Analysis of Mixing Oil (Diala B with S2-ZUI) for Cooling Systems Used in Power Transformers. Issue 1 (March 2021) - Hs, Syafruddin; Supriyadi,; Pinem, Maksum
Abstract: The Diala B oil used as a cooling system for transformers is an old product from the manufacturer and is no longer being reproduced. To maintain the oil level in the transformer under normal conditions, S2-ZUI oil is added which is a new product from the manufacturer. Before being mixed with old oil, new oil is tested in the laboratory to meet the test parameters in the IEC 60296 standard. In this paper, several important parameters are measured such as viscosity, breakdown voltage, water content, acidity, density, flash point, pour point, corrosive sulfur, interfacial tension, dielectric dissipation factor, total acidity, and sludge. Besides, the properties of mixed oil are also tested in the laboratory before mixing them in the transformer. The results showed that the new oil (100% S2-ZUI) and the mixture of Diala B with S2-ZUI (50%: 50%) tested in the laboratory still meet the quality requirements according to IEC 60296 standards. Laboratory test results indicate that this new oil can be used as an addition to Diala B oil in transformers for cooling and insulation systems.